The Prospect of Rooftop Photovoltaic Development Considering Global Horizontal Irradiation Uncertainty and Government Policies: A Case of Java Island, Indonesia - Firmansyah Setya Budi, Rizki; Sarjiya, Sarjiya; Pramoho Hadi, Sasongko (International Journal of Energy Economics and Policy, 2022)
Global horizontal irradiation uncertainty and government policy significantly affect the economics of rooftop photovoltaic development. Unfortunately, previous studies neglect these aspects. Therefore, it is necessary to undertake the economic analysis of rooftop photovoltaic development by considering its global horizontal irradiation uncertainty and government policies. This research creates a model that can be used to perform analysis and assess rooftop photovoltaic development prospects by considering irradiation uncertainty and government policies. The attractiveness of rooftop photovoltaic development is indicated by the value of the Levelized cost of electricity, net present value, and internal rate of return. Monte Carlo simulation models irradiation uncertainty. Java Island in Indonesia is used as a case study to show the performance of the proposed model. The research results show that the rooftop photovoltaic is not economically viable if built by the utility. Rooftop photovoltaic systems are only profitable when built by the private sector and is used for internal usage only. These rooftop photovoltaic investments provide an internal rate of return above 14%, which shows that investors with green capital funds and local investors are interested in investing. The emission reductions from a 100 m2 rooftop photovoltaic system vary from 214 to 384 tons of CO2 per year.